Effects of Ocean Acidification on Molting, Oxidative Stress, and Gut Microbiota in Juvenile Horseshoe Crab Tachypleus tridentatus - Liu, Ximei; Liu, Jiani; Xiong, Kai; Zhang, Caoqi; Fang, James Kar-Hei; Song, Jie; Tai, Zongguang; Zhu, Quangang; Hu, Menghong; Wang, Youji (Frontiers in Physiology, 2022)
Anthropogenic elevation of atmospheric carbon dioxide (CO2) drives global-scale ocean acidification (OA), which has aroused widespread concern for marine ecosystem health. The tri-spine horseshoe crab (HSC) Tachypleus tridentatus has been facing the threat of population depletion for decades, and the effects of OA on the physiology and microbiology of its early life stage are unclear. In this study, the 1st instar HSC larvae were exposed to acidified seawater (pH 7.3, pH 8.1 as control) for 28 days to determine the effects of OA on their growth, molting, oxidative stress, and gut microbiota. Results showed that there were no significant differences in growth index and molting rate between OA group and control group, but the chitinase activity, β-NAGase activity, and ecdysone content in OA group were significantly lower than those of the control group. Compared to the control group, reactive oxygen species (ROS) and malondialdehyde (MDA) contents in OA group were significantly increased at the end of the experiment. Superoxide dismutase (SOD), catalase (CAT), and alkaline phosphatase (AKP) activities increased first and then decreased, glutathione peroxidase (GPX) decreased first and then increased, and GST activity changed little during the experiment. According to the result of 16S rRNA sequencing of gut microbiota, microbial-mediated functions predicted by PICRUSt showed that “Hematopoietic cell lineage,” “Endocytosis,” “Staphylococcus aureus infection,” and “Shigellosis” pathways significantly increased in OA group. The above results indicate that OA had no significant effect on growth index and molting rate but interfered with the activity of chitinolytic enzymes and ecdysone expression of juvenile horseshoe crabs, and caused oxidative stress. In addition, OA had adverse effects on the immune defense function and intestinal health. The present study reveals the potential threat of OA to T. tridentatus population and lays a foundation for the further study of the physiological adaptation mechanism of juvenile horseshoe crabs to environmental change.